IMPLICATIONS OF THE TEACHER’S CHARACTER IN FORMATION OF STUDENT’S CHARACTER (STUDY FROM THE PERSPECTIVE OF IMAM NURUDDIN AL SAMHUDI IN THE BOOK OF JAWAHIR AL-'IQDAIN FI FADHLI ASY-SARAFAIN) - Asyrul Zulmi Noor (Pascasarjana Universitas Wahid hasyim Semarang, 2023)
ABSTRACTThe National Education System states that the education in question is an education based onreligious spiritual values and prioritizes personality and noble moral character, not only prioritizingknowledge and logical intelligence. The spearhead of achieving this goal is certainly one of them isin the hands of teachers as exemplary figures in forming good participant characters in accordancewith the demands of the national education system. Among the classical clerical figures who discussthe character of the teacher is Imam al Samhudi.This research aims to find out how the implications of Imam al Samhudi's thinking about thecharacter that a teacher must have on the formation of good character of learners. This research usesdescriptive research methods and content analysis. Data collection techniques use literature studiesand documentation. The results of this study revealed the conclusion that Imam al Samhudi'sthoughts have very good implications if they can really be applied by all teachers in the nationaleducation system, especially in terms of the formation of the character of learners in accordancewith the demands of character education development.Keywords: Teacher Character, Student Character, Imam al Samhudi